Synthesis of a hexasaccharide partial sequence of hyaluronan for click chemistry and more - Marina Bantzi; Stephan Rigol; Athanassios Giannis (Beilstein Journal of Organic Chemistry, 2015)
In the present work, the synthesis of a hexasaccharide partial sequence of hyaluronan equipped with a terminal azido moiety is reported. This hexasaccharide can be used for the attachment on surfaces by means of click chemistry and after suitable deprotection for biophysical studies.